Strain Selection, Biomass to Biofuel Conversion, and Resource Colocation have Strong Impacts on the Economic Performance of Algae Cultivation Sites - Venteris, Erik R.; Wigmosta, Mark S.; Coleman, Andre M.; Skaggs, Richard L. (Frontiers in Energy Research, 2014)
Decisions involving strain selection, biomass to biofuel technology, and the location of cultivation facilities can strongly influence the economic viability of an algae-based biofuel enterprise. We summarize our past results in a new analysis to explore the relative economic impact of these design choices. Our growth model is used to predict average biomass production for two saline strains (Nannocloropsis salina, Arthrospira sp.), one fresh to brackish strain (Chlorella sp., DOE strain 1412), and one freshwater strain (order Sphaeropleales). Biomass to biofuel conversion is compared between lipid extraction (LE) and hydrothermal liquefaction (HTL) technologies. National-scale models of water, CO2 (as flue gas), land acquisition, site leveling, construction of connecting roads, and transport of HTL oil to existing refineries are used in conjunction with estimates of fuel value (from HTL) to prioritize and select from 88,692 unit farms (UF, 405 ha in pond area), a number sufficient to produce 136E+9 L yr-1 of renewable diesel (36 billion gallons yr-1). Strain selection and choice of conversion technology have large economic impacts, with differences between combinations of strains and biomass to biofuel technologies being up to 10 million dollars yr-1 UF-1. Results based on the most productive strain, HTL-based fuel conversion, and resource costs show that the economic potential between geographic locations within the selection can differ by up to 4 million yr-1 UF-1, with 1.8 BGY of production possible from the most cost-effective sites. The local spatial variability in site rank is extreme, with very high and low sites within 10s of km of each other. Colocation with flue gas sources has a strong influence on rank, but the most costly resource component varies from site to site. The highest rank UFs are located predominantly in Florida and Texas, but most states south of 37°N latitude contain promising locations.